Causes and consequences of variation in plant population growth rate: a synthesis of matrix population models in a phylogenetic context - Yvonne M. Buckley; Satu Ramula; Simon P. Blomberg; Jean H. Burns; Elizabeth E. Crone; Johan Ehrlén; Tiffany M. Knight; Jean‐Baptiste Pichancourt; Helen Quested; Glenda M. Wardle (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1182–1197 Abstract Explaining variation in population growth rates is fundamental to predicting population dynamics and population responses to environmental change. In this study, we used matrix population models, which link birth, growth and survival to population growth rate, to examine how and why population growth rates vary within and among 50 terrestrial plant species. Population growth rates were more similar within species than among species; with phylogeny having a minimal influence on among‐species variation. Most population growth rates decreased over the observation period and were negatively autocorrelated between years; that is, higher than average population growth rates tended to be followed by lower than average population growth rates. Population growth rates varied more through time than space; this temporal variation was due mostly to variation in post‐seedling survival and for a subset of species was partly explained by response to environmental factors, such as fire and herbivory. Stochastic population growth rates departed from mean matrix population growth rate for temporally autocorrelated environments. Our findings indicate that demographic data and models of closely related plant species cannot necessarily be used to make recommendations for conservation or control, and that post‐seedling survival and the sequence of environmental conditions are critical for determining plant population growth rate.

Leaf traits capture the effects of land use changes and climate on litter decomposability of grasslands across Europe - Claire Fortunel; Eric Garnier; Richard Joffre; Elena Kazakou; Helen Quested; Karl Grigulis; Sandra Lavorel; Pauline Ansquer; Helena Castro; Pablo Cruz; JiŘí DoleŽal; Ove Eriksson; et al. (Ecology, 2009)
Land use and climate changes induce shifts in plant functional diversity and community structure, thereby modifying ecosystem processes. This is particularly true for litter decomposition, an essential process in the biogeochemical cycles of carbon and nutrients. In this study, we asked whether changes in functional traits of living leaves in response to changes in land use and climate were related to rates of litter potential decomposition, hereafter denoted litter decomposability, across a range of 10 contrasting sites. To disentangle the different control factors on litter decomposition, we conducted a microcosm experiment to determine the decomposability under standard conditions of litters collected in herbaceous communities from Europe and Israel. We tested how environmental factors (disturbance and climate) affected functional traits of living leaves and how these traits then modified litter quality and subsequent litter decomposability. Litter decomposability appeared proximately linked to initial litter quality, with particularly clear negative correlations with lignin‐dependent indices (litter lignin concentration, lignin : nitrogen ratio, and fiber component). Litter quality was directly related to community‐weighted mean traits. Lignin‐dependent indices of litter quality were positively correlated with community‐weighted mean leaf dry matter content (LDMC), and negatively correlated with community‐weighted mean leaf nitrogen concentration (LNC). Consequently, litter decomposability was correlated negatively with community‐weighted mean LDMC, and positively with community‐weighted mean LNC. Environmental factors (disturbance and climate) influenced community‐weighted mean traits. Plant communities experiencing less frequent or less intense disturbance exhibited higher community‐weighted mean LDMC, and therefore higher litter lignin content and slower litter decomposability. LDMC therefore appears as a powerful marker of both changes in land use and of the pace of nutrient cycling across 10 contrasting sites.

Parasitic plants—impacts on nutrient cycling - Helen M. Quested (Plant and Soil, 2008)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Litter of the hemiparasite Bartsia alpina enhances plant growth: evidence for a functional role in nutrient cycling - Helen M. Quested; Malcolm C. Press; Terry V. Callaghan (Oecologia, 2003)

The hemiparasitic angiosperm Bartsia alpina has the potential to accelerate decomposition in sub-arctic communities - Helen M. Quested; Malcolm C. Press; Terry V. Callaghan; Hans J. Cornelissen (Oecologia, 2002)